2016
DOI: 10.18632/oncotarget.13524
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol import and steroidogenesis are biosignatures for gastric cancer patient survival

Abstract: Androgens, estrogens, progesterone and related signals are reported to be involved in the pathology of gastric cancer. However, varied conclusions exist based on serum hormone levels, receptor expressions, and in vitro or in vivo studies. This report used a web-based gene survival analyzer to evaluate biochemical processes, including cholesterol importing via lipoprotein/receptors (L/R route), steroidogenic enzymes, and steroid receptors, in gastric cancer patients prognosis. The sex hormone receptors (androge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 42 publications
2
50
0
Order By: Relevance
“…In summary, our study showed that cholesterol supply promotes GCa progression , while de novo cholesterol synthesis is irrelevant to GCa progression. These results are consistent with those of Yorket al (2015), who found that cholesterol influx is reduced by activating type I IFN signaling in cancer .…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In summary, our study showed that cholesterol supply promotes GCa progression , while de novo cholesterol synthesis is irrelevant to GCa progression. These results are consistent with those of Yorket al (2015), who found that cholesterol influx is reduced by activating type I IFN signaling in cancer .…”
Section: Discussionmentioning
confidence: 53%
“…In previous work, we developed a formula to calculate the impact of genes on different GCa conditions with the KM plotter survival analyzer :HR score=(Avg. of HR of gene sets)=1.2em1.2emtrue(HRn11.2em1.2emtrue)×1.2em1.2emtrue(log101.2em1.2emtrue(pvalue1.2em1.2emtrue)1.2em1.2emtrue)italicn…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following formula was used to calculate HR scores20: HR score=Avg. HR score of gene sets=false(HRn1false)×false(log10(Pvalue)false)normaln×100 …”
Section: Methodsmentioning
confidence: 99%
“…There are online databases to validate the importance of gene expressions in BCA patient survival (http://kmplot.com/analysis/index.php?p=service&cancer=breast). Beneficiary from the advances of bioinformatics, using the web‐based genome‐scale gene expression survival analyzer followed with pathway weighting algorithm, we are able to evaluate gene clusters/pathways‐of‐genes in cancer patient prognosis in a hypothesis‐driven basis 20. To test our hypothesis, we performed Kaplan Meier plotter to investigate the role of S1P in BCA patient survival (http://kmplot.com/analysis/index.php?p=service&cancer=breast) and the association between S1P metabolism and BCA progression.…”
Section: Introductionmentioning
confidence: 99%